Mechanical Behavior of Hollow Shaft and Sleeve with Interference Fit and Axial Tensile Load in Textile Machinery (Journal of Fiber Bioengineering and Informatics, 2014)
Interference fit is one of the most common assembly methods in textile machinery, this paper focuses onthe interference assembly of hollow shaft and sleeve. The mechanical behaviors of hollow shaft and sleevewere investigated by using the finite element method under interference fit and axial tension load. Theeffects of interference, hollow degree, axial load, friction coefficient, sleeve thickness on the mechanicalproperty were studied. The results show that there is still an “end effect” of the contact stress andequivalent stress of the sleeve under axial load. Maximum equivalent stress of hollow shaft appearson the inside cylindrical surface under tensile loading. Under axial tensile load, contact stress and theequivalent stress of sleeve increases with the increasing of interference, sleeve thickness, and decreaseswith the increasing of hollow degree and load. The equivalent stress of hollow shaft increases with theincreasing of the four parameters. The friction coefficient has a very small effect on the mechanicalproperty.